Current technologies for the endoscopic assessment of duodenal villous pattern in celiac disease. (1st October 2015) - Ianiro, Gianluca; Bibbò, Stefano; Pecere, Silvia; Gasbarrini, Antonio; Cammarota, Giovanni
Abstract: Currently, standard endoscopy is not considered enough reliable for the evaluation of celiac disease, neither to drive biopsy sampling. The diagnostic reliability of the endoscopic assessment of celiac disease has been increased by the recent advancement of software and hardware technologies. Several endoscopic technologies have been investigated so far for the diagnostic evaluation of celiac disease, including: water-immersion techniques, dye-based and dye-less chromoendoscopy techniques (Narrow band imaging; Fujinon Intelligeng Chromo Endoscopy; I-scan); optical coherence tomography; confocal laser endomicroscopy; high-resolution magnification endoscopy; videocapsule endoscopy; enteroscopy. Such a technologic improvement brought us to higher diagnostic possibilities in the evaluation and management of CD. A wider application of advanced diagnostic endoscopic techniques is therefore warranted to decrease the number of misdiagnoses and related healthcare costs of celiac disease.